Relationship of severity pruning and weather variables on quality fruit production of ber (Ziziphus mauritiana L. cv. Sanaur-2) - Khokhar, Yogesh (Bangladesh Journal of Botany, 2020)
Pruning had a vital role on the quality of fruit production in ber fruit crop under lower Shiwaliks of Punjab. The severity of pruning intensity significantly influenced the tree vegetative growth parameters and flowering behaviour of ber cv. Sanaur-2 viz. number of emerged shoots per branch, shoot length and girth of primary shoot. A significant higher percentage of fruit set, fruit retention, higher percentage of ‘A’ grade fruits and other fruit quality parameters viz., fruit weight, TSS, acidity, vitamin C, total sugars was recorded significantly higher in pruning treatment by removal 50 per cent vegetative growth over other treatments. Powdery mildew incidence steadily increased from standard meteorological weeks (SMW) 36 - 39 to 40 - 43 and then decreased under different pruning treatments. The severity of pruning reduces the incidence of powdery mildew. The meteorological knowledge on various weather variables at 3 - 4 weeks to actual incidence also can be effectively used to check the spread and severity of the disease.